Preparation of calcium oxide from cattle bones as catalyst for conversion of waste cooking oil to biodiesel - Sabat Okta Ceria Sitompul; Risfidian Mohadi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2017)
Preparation of calcium oxide from cattle bones by thermal decomposition for 3 hours using various temperature at 400°, 500°, 800°, 900°, 1000°, and 1100°C. Calcium oxide was characterized using X-Ray Diffractometer. The results of XRD pattern showed of diffraction similar to CaO standard from JCPDS at 2θ: 32.2°; 37.3°; 53.8°; 64.1° and 67.3°. The CaO from heating cattle bones at 1000°C resulting of 2θ: 32.3°; 53.8° and 64.1°. Then, the metal oxide was characterized by FT-IR which showed the existence of CaO at wave number 362.2 cm-1 from CaO vibration. The CaO from cattle bones applied as catalyst on biodiesel synthesis from waste cooking oil and resulting viscosity value of biodiesel 5.93 cSt, density 0.876 g/cm3, acid value 0.561 mg/KOH and iod number value 16.92 g/100 g, respectively all in the range of SNI standard. Keywords: cattle bones, calcium oxide, catalyst, biodiesel, waste cooking oil.